Endocannabinoid signaling at the periphery: 50 years after THC. (May 2015) - Maccarrone, Mauro; Bab, Itai; Bíró, Tamás; Cabral, Guy A.; Dey, Sudhansu K.; Di Marzo, Vincenzo; Konje, Justin C.; Kunos, George; Mechoulam, Raphael; Pacher, Pal; Sharkey, Keith A.; Zimmer, Andreas
Highlights Fifty years ago the psychoactive ingredient of Cannabis sativa, THC, was isolated. We critically review the current status of eCB function in peripheral organs. We discuss the relevance of the peripheral ECS in human health and disease pathogenesis. We highlight emerging challenges and therapeutic hopes.